2005
DOI: 10.2113/176.3.301
|View full text |Cite
|
Sign up to set email alerts
|

Paleoenvironments, paleoclimates and sequences of Westphalian deposits of Lorraine coal basin (Upper Carboniferous, NE France)

Abstract: Facies and sequences of the Westphalian C are identified in cores and well logs of three boreholes and three seismic lines supplied by Conoco-Phillips from the Lorraine coal Basin. The lithofacies associations suggest various paleoenvironments and sequences during the Westphalian C. Decameter-thick sedimentary bodies display alluvial fan deposits in the northwestern border of the basin (Chaumont borehole). Decametric sedimentary bodies constituted either of conglomeratic and sandy facies with cylindrical shape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…In the part of the Lorraine coal Basin that was operated by HBL (Lorraine coal Basin company) close to the Saar, the stratigraphy was established with paleoflora sampled in coal mines and boreholes by HBL geologists and Laveine (1974). In the part of Lorraine without coal mines, the stratigraphy of seismic lines in Lorraine was done in using the logs of boreholes (Izart et al, 2005) and our interpretation. The paleoenvironments were determined from cores and logs of borehole by Izart et al (2005).…”
Section: 2) Stratigraphymentioning
confidence: 99%
“…In the part of the Lorraine coal Basin that was operated by HBL (Lorraine coal Basin company) close to the Saar, the stratigraphy was established with paleoflora sampled in coal mines and boreholes by HBL geologists and Laveine (1974). In the part of Lorraine without coal mines, the stratigraphy of seismic lines in Lorraine was done in using the logs of boreholes (Izart et al, 2005) and our interpretation. The paleoenvironments were determined from cores and logs of borehole by Izart et al (2005).…”
Section: 2) Stratigraphymentioning
confidence: 99%
“…The LCB is an intra-mountain coal depression formed during the Hercynian Orogeny between Carboniferous and Permian (Donsimoni, 1981) and interpreted as a strike-slip basin (Korsch and Schäfer, 1995;Izart et al, 2005). This context has favoured organic matter-rich clastic deposits.…”
Section: Geological Settingsmentioning
confidence: 99%
“…The anaerobic decomposition of organic matter in water has produced the coal bearing deposits of the Westphalian and Stephanian age (Carboniferous -equivalent of the Pennsylvanian age in ICS-stage) (e.g. Izart et al, 2005). They consist of intercalated beds in a complex sequence of claystones, sandstones, and conglomerates that show lateral variations both in terms of nature and thickness.…”
Section: Geological Settingsmentioning
confidence: 99%
“…In the Westphalian, sediment supply was mainly from the Hunsrück and the Taunus provenance provinces or broadly speaking from the Rhenish Massif, which has been served as an uplifted shoulder of the rift. Izart et al [14] showed that continental deposits and third to second order sequences of the Lorraine Basin during this stage were mainly controlled by tectonics that generated the accommodation space in the basin during the subsidence and the maximum flooding periods. [14] as clear unconformity.…”
Section: Fig5 Geological Framework Of the Basin And The Kinematic Pmentioning
confidence: 99%